(untitled) (Research, Society and Development, 2023)
Objective: to identify the contributions of psychology to the mental health of homoaffective elderly people, through a literature review. Methodology: for research development, articles were searched in electronic databases: Google Scholar, Periodicals CAPES, SciELO, PubMed, MEDLINE and Lilacs, from 2009 to April 2022, in addition, books were used for the theoretical foundation. Results and discussion: From the data analysis, it was shown that the elderly themselves and society in general make up representations about sexuality in old age, the subject acquires more resistance when it comes to homoaffective elderly people, since the quality of life of this group is related to the experience or not of homoaffective relationships and their exposure to society, psychology proved to be very important for the researched group, since they present significant mental suffering. Final considerations: further study is needed on the subject with a larger number of participants.